Synthesis, characterization and corrosion inhibition study of schiff base ligands in 1 M HCL / Cordelia Abdul Rahim - Abdul Rahim, Cordelia (Faculty of Applied Sciences, 2009)
This study has been done to synthesize, characterize and to investigate the efficiency as a corrosion inhibiting compound of the Schiff base ligands for mild steel. Schiff base has been known as an alternative that can be applied in the industry to reduce the rate of corrosion which is cheap as well. The chemicals used were o-phenyldiamine, ethylenediamine, benzaldehyde and benzalacetophenone which resulted in three Schiff Base ligands were obtained. These ligands were then characterized to confirm the purity of the compound obtained with its predicted properties. Then these Schiff base ligands were applied in the corrosion test using the weight loss method in an acidic media of 1 M of hydrochloric acid (HCL). The data collected over the period of five days were then calculated and analyzed. The result shows that the Schiff base ligands were proven to effectively inhibit the corrosion process. This can be concluded that the Schiff Base ligands are an effective corrosion inhibitor.